The Interconnected Magmatic Plumbing System of the Natron Rift - M. C. Reiss; L. DeSiena; J. D. Muirhead (Geophysical Research Letters)
Abstract Understanding the magmatic plumbing system of rift volcanoes is essential when examining the interplay between magmatic and tectonic forces. Recent seismicity, volcanic activity, magma emplacement, and volatile release make the Natron basin the ideal location to study these processes in the East African Rift System. Here, we present the first high‐resolution tomographic imaging of Oldoinyo Lengai volcano and surrounding volcanic systems using attenuation mapping. High scattering and absorption features reveal fluid‐filled fracture networks below regions of magmatic volatile release at the surface and a close spatial association between carbonatite volcanism and deeply penetrating, fluid‐filled faults. High‐absorption features appear sensitive to fluids and thermal gradients, revealing a central sill complex and connected plumbing system down to the mid‐crust, which links volcanoes and rift segments across the developing magmatic rift.